(untitled) (International Journal of Innovative Research in Engineering & Management, 2024)
Against the backdrop of growing global climate concerns, this study attempts to comprehensively explore the impacts of climate change in the Jangal Mahal forest region of West Bengal, India through the perception of forest dependent communities. In this context, we have attempted to address climate change perceptions regarding impacts on forest ecosystems through descriptive statistics. We used primary data collected randomly from 241 households in 8 blocks of Jangal Mahal region of West Bengal. Data collection in this study was through questionnaire based personal in depth interviews. We selected 10 indicators to measure household perceptions of climate change and the impacts of climate change on forests. The results show that households strongly agree with the increase in average temperature, increase in hot days, unpredictability of rainfall and climate change events but strongly disagree with changes in withdrawal of monsoon, longer winter season and increase in rainfall. It has also been observed that climate change is having severe negative impact on Non-timber forest product (NTFP) quality, soil fertility, wood supply, mortality of native plant species and forest density, but no serious impact on forest biological systems.